A comparison of the effectiveness of Samarthram vacuum suction cannula with uterotonic drugs as primary management in cases of atonic PPH at tertiary care center: a randomized clinical trial - Raghuwanshi, Neethika; Sirsam, Shyamkumar; Tambe, Sneha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Atonic PPH is a leading cause of maternal mortality. The SR cannula offers a low-cost, practical alternative by creating negative intrauterine pressure that mimics natural uterine retraction. To compare effectiveness of SR vacuum suction cannula and with uterotonic drugs in cases of Atonic PPH. Methods: This prospective study at GMC Akola enrolled 100 women developing atonic PPH after AMTSL. Patients were randomized to SR cannula (n=50) or uterotonics (n=50). Group A: Cannula inserted up to fundus, negative suction at 650 mmHg for 10 min, repeated hourly 3 times. Group B: Uterotonics given as needed sequentially (Methergine → Carbetocin→Misoprostol→Carboprost) with 15-min interval. All patients were observed for bleeding, tone, vitals; Results: In Group A (SR cannula), bleeding stopped in <4 min in 64%, 5-9 min in 26%, 10-14 min in 4% and >14 min in 6%. In Group B (uterotonics),in 6%, 52%, 30% and 12% respectively. Mean blood loss was 302.85±106.07ml in Group A vs 377.9±135.41ml in Group B. Conclusions: SR cannula is as effective as uterotonics for atonic PPH, with faster bleeding control, lower cost, reusability and transport feasibility, yet larger studies are needed for validation.